2010
DOI: 10.1186/1471-2431-10-8
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial dysfunction in obese non-hypertensive children without evidence of sleep disordered breathing

Abstract: BackgroundEndothelial dysfunction is a complication of both obesity and obstructive sleep apnea syndrome (OSAS), the latter being highly prevalent among obese children. It is unknown whether obesity causes endothelial dysfunction in children in the absence of OSAS. This study examines endothelial function in obese and non-obese children without OSAS.MethodsPre-pubertal non-hypertensive children were recruited. Endothelial function was assessed in a morning fasted state, using a modified hyperemic test involvin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 33 publications
3
39
0
3
Order By: Relevance
“…25 Sleep architecture, respiratory events, and arousals were scored using standard pediatric criteria. 26 Apneas were defined as $ 90% airflow decrement lasting at least two breaths, and hypopneas were defined as > 50% decrement in nasal airflow accompanied by a 3% desaturation and/or an EEG arousal.…”
Section: Methodsmentioning
confidence: 99%
“…25 Sleep architecture, respiratory events, and arousals were scored using standard pediatric criteria. 26 Apneas were defined as $ 90% airflow decrement lasting at least two breaths, and hypopneas were defined as > 50% decrement in nasal airflow accompanied by a 3% desaturation and/or an EEG arousal.…”
Section: Methodsmentioning
confidence: 99%
“…11,12 We have recently shown that obesity in children is associated with an increased risk for the development of endothelial dysfunction prior to the onset of hypertension. 13 Indeed, using a modifi ed hyperemic test after cuffinduced occlusion of the radial and ulnar arteries, we demonstrated that signifi cant delays occur in the vascular reperfusion kinetics among children who were obese and nonhypertensive and who did not suffer from either diabetes or obstructive sleep apnea (OSA). 13 The exclusion of OSA 13 is particularly relevant, considering that obesity markedly increases the risk for sleep-disordered breathing.…”
Section: Sphygmomanometrymentioning
confidence: 99%
“…13 Indeed, using a modifi ed hyperemic test after cuffinduced occlusion of the radial and ulnar arteries, we demonstrated that signifi cant delays occur in the vascular reperfusion kinetics among children who were obese and nonhypertensive and who did not suffer from either diabetes or obstructive sleep apnea (OSA). 13 The exclusion of OSA 13 is particularly relevant, considering that obesity markedly increases the risk for sleep-disordered breathing. [14][15][16] OSA is a highly prevalent condition in children, in which intermittent occlusion of the upper airway during sleep leads to recurrent oxyhemoglobin desaturations, elevated CO 2 levels, sleep fragmentation, and reduced sleep effi ciency.…”
Section: Sphygmomanometrymentioning
confidence: 99%
See 1 more Smart Citation
“…5 Furthermore, the concurrent presence of obesity and OSA magnifi ed the severity of endothelial dysfunction, thereby reinforcing the assumption that both conditions will impose incremental, long-term cardiovascular risk. [6][7][8] However,…”
mentioning
confidence: 99%